ECONOMIC TRAINING OF ETHNIC GROUPS OF THE SURKHON OASIS - Sobirov Jamshidbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
all elate and peoples of the world have gone through a rather complex ethnic process. Because each Ethnos has been formed during a long historical period as a result of contact with different Ethnos, sometimes moving from one place to another, mixing with other Ethnos, absorbing them, or making their components. And this article will talk about the economic training of the ethnic groups of the Surkhon Oasis.